1] y - 3x = -8
[2] y + 9x = 4
-3x + y = -8 9x + y = 4
Solve equation [2] for the variable y
[2] y = -9x + 4
// Plug this in for variable y in equation [1]
[1] (-9x+4) - 3x = -8
[1] - 12x = -12
// Solve equation [1] for the variable x
[1] 12x = 12
[1] x = 1
// By now we know this much :
y = -9x+4
x = 1
// Use the x value to solve for y
y = -9(1)+4 = -5
{y,x} = {-5,1}
Answer:
15b + 30
Step-by-step explanation:
By expansion (6 x 2.5b) + (6 x 5)
= 15b + 30
Paul must get 13 since Peter gets more more than Jane so Jane would get 7 and then peter would get 12